A Multiple Solutions Approach to the Inverse Kinematics Problem of a General Serial Manipulator. Issue 1 (August 2021) - Fan, Yanping; Li, Pin; Zhen, Xijin; Shen, Zongbao
Abstract: The inverse kinematics problem (IKP) is at the center of computer control algorithms for general serial manipulator. The exact number of feasible solutions of the IKP is highly dependent on the manipulator structure as well as the desired end-effector pose, and the existing inverse kinematics methods have difficulties to solve all feasible solutions of a general serial manipulator. In this work, a multiple solutions approach is applied to the IKP. Then, three numerical examples are used to validate the effectiveness of the multiple solutions approach, and the numerical results demonstrate that the multiple solutions approach is effective and practicable. Finally, an infinite solutions example is presented to show that the proposed approach could also provide limited number of numerical solutions in singularity.